2020
DOI: 10.1111/hepr.13537
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of lenvatinib in hepatocellular carcinoma patients with portal hypertension

Abstract: Aim Preserved liver function may be an important factor affecting therapeutic efficacy in hepatocellular carcinoma patients treated with lenvatinib, but not all patients can be treated while preserving liver function. This study evaluated the therapeutic efficacy of lenvatinib in patients with poor liver function with and without portal hypertension. Methods This prospectively registered multicenter study analyzed 93 patients treated with lenvatinib. Progression‐free survival was compared between patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…33,35 In a prospective multicenter study of 93 patients treated with lenvatinib, in which 37 patients had advance portal hypertension, OS did not seem to be compromised by advanced portal hypertension. 36 On the contrary, the risk of variceal bleeding was elevated in IMbrave 150 at 2.4% in the atezolizumab plus bevacizumab group compared to 0.6% in the sorafenib group. Of note, this was a group of well-selected patients benefited from optimal portal hypertension prophylaxis and patients with bleeding esophageal or gastric varices have been excluded from the study already.…”
Section: Patients With Severe Portal Hypertension or Main Portal Vein...mentioning
confidence: 93%
See 1 more Smart Citation
“…33,35 In a prospective multicenter study of 93 patients treated with lenvatinib, in which 37 patients had advance portal hypertension, OS did not seem to be compromised by advanced portal hypertension. 36 On the contrary, the risk of variceal bleeding was elevated in IMbrave 150 at 2.4% in the atezolizumab plus bevacizumab group compared to 0.6% in the sorafenib group. Of note, this was a group of well-selected patients benefited from optimal portal hypertension prophylaxis and patients with bleeding esophageal or gastric varices have been excluded from the study already.…”
Section: Patients With Severe Portal Hypertension or Main Portal Vein...mentioning
confidence: 93%
“…However, bleeding events related to portal hypertension with the use of MTIs (including lenvatinib) were consistently reported to be lower than 2% in the recent published phase 3 trials [ 33 , 35 ]. In a prospective multicenter study of 93 patients treated with lenvatinib, in which 37 patients had advance portal hypertension, OS did not seem to be compromised by advanced portal hypertension [ 36 ]. On the contrary, the risk of variceal bleeding was elevated in IMbrave 150 at 2.4% in the atezolizumab plus bevacizumab group compared to 0.6% in the sorafenib group.…”
Section: Lenvatinib Monotherapy As First-line Treatment In Advanced Hccmentioning
confidence: 99%
“…It is interesting to point out that PH may affect the efficacy of systemic therapy. A prospective multicenter study showed that Lenvatinib prolonged progression-free survival in patients with more severe PH and poorer liver function expressed as albumin-bilirubin score (ALBI) grade 2 or 3, reflecting an increased effect related to changes in drug pharmacokinetics and exposure [76].…”
Section: Effect Of Lenvatinib On Portal Hypertensionmentioning
confidence: 99%